Echocardiography - Nihoyannopoulos, Petros; Kisslo, Joseph (Springer London : Imprint: Springer, 2009)
Echocardiography has expanded greatly to become a sub-specialty in cardiology in its own right. From the original M-mode modality of 50 years ago, it has evolved into a complex multimodality method for evaluating and quantifying cardiovascular lesions. In addition, the entire spectrum of hemodynamic assessment of the heart can now be performed noninvasively using echocardiography alone. Transesophageal echocardiography has added to the clarity of imaging and proved to be extremely helpful In valve surgery. Lately, three-dimensional echocardiography has added a new dimension and helped the understanding of cardiac anatomy and pathology in real time. Finally, deformation imaging and assessment of myocardial perfusion completes the global assessment of the heart by echocardiography by looking at the various contraction and perfusion patterns in patients with coronary artery disease at rest and during stress. Echocardiography highlights the clinical utility of these evolving modalities that are now crucial to the renaissance of echocardiography. Thus it provides a thorough clinical review of this most revealing and adaptable methods of imaging a patient. The Editors and their world-class group of contributors have created an essential reference for all who use echocardiography in the practice.